ANALISIS PENGARUH FEE AUDIT, REPUTASI AUDITOR, TERHADAP KUALITAS AUDIT DENGAN AUDIT DELAY SEBAGAI VARIABEL MODERASI - Juniarto, Antonius; Prathivi, Maria Dini Gilang (FEB Universitas Sam Ratulangi Manado, 2024)
In this adult and business world, the development of the business world and business is very fast and everyone is competing. Companies must continue to innovate for survival and must even present good and correct financial reports. One thing that can be done is to conduct an audit as a third party with integrity. The study was conducted using SmartPLS testing. This study aims to test the effect of audit fees and audit reputation on audit delay and audit quality, as well as the role of audit delay as a moderating variable. The results of the study indicate that audit fees have a significant effect on audit delay with a negative relationship, while audit reputation has a positive and significant effect on audit delay. Audit delay also affects audit quality significantly with a negative relationship. Audit fees affect audit quality but with a negative relationship. Audit reputation has a positive effect on audit quality. However, audit delay is unable to moderate the relationship between audit fees and audit quality, but is able to moderate the relationship between audit reputation and audit quality significantly with a negative relationship direction.